If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + 6a + b + 2b = 0 Combine like terms: a + 6a = 7a 7a + b + 2b = 0 Combine like terms: b + 2b = 3b 7a + 3b = 0 Solving 7a + 3b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3b' to each side of the equation. 7a + 3b + -3b = 0 + -3b Combine like terms: 3b + -3b = 0 7a + 0 = 0 + -3b 7a = 0 + -3b Remove the zero: 7a = -3b Divide each side by '7'. a = -0.4285714286b Simplifying a = -0.4285714286b
| 5x+19=61-2x | | 5x-4=4-x | | 8x^3+5x^3+7= | | y=8-0.4x | | 6x+21=13x+56 | | 7x+13=10x-5 | | 2000000x^4=80000 | | 372=2L+176 | | (8+4)x^3+8= | | 2(x-12)=3(x+5) | | 7s+5=26 | | -7(4.5v-3.5)=27.5-5.5v | | 372=2L+88 | | x^4=.04 | | 3+4(2x-3)=7 | | 5+3(2x-7)=5+6x-21 | | 24a-48=18a-36 | | 8x^3+4x^3+8= | | y=1.03 | | -4x-10=4(5x-4) | | 5xy-3b=11 | | 4-9x=y | | f(5)=10 | | 10x-2=-4x+10 | | D-6pie=pie | | 6x+12=(-12) | | 7-4(d-30)=23 | | -6s+8.5+5.5s=24.5 | | 2(x^2+10-25)=0 | | 3g+4(-8+2g)=1g | | 45+x=(13+x)+(4+x)+(10+x) | | 5+12-1=0 |